2019
DOI: 10.1128/jvi.01621-18
|View full text |Cite
|
Sign up to set email alerts
|

Splicing-Dependent Subcellular Targeting of Borna Disease Virus Nucleoprotein Isoforms

Abstract: Targeting of viral proteins to specific subcellular compartments is a fundamental step for viruses to achieve successful replication in infected cells. Borna disease virus 1 (BoDV-1), a nonsegmented, negative-strand RNA virus, uniquely replicates and persists in the cell nucleus. Here, it is demonstrated that BoDV nucleoprotein (N) transcripts undergo mRNA splicing to generate truncated isoforms. In combination with alternative usage of translation initiation sites, the N gene potentially expresses at least si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 54 publications
0
4
0
Order By: Relevance
“…While BoDV-2 N contains 6 amino acid differences and an amino acid deletion not shared with BoDV-1 N (Fig. 2A), in addition to NLS and NES, which determine the intracellular localization of N (21,22), four amino acid residues thought to interact with viral RNA (29) are completely conserved in BoDV-2 N. Moreover, a downstream start codon and splicing donor and acceptor sites that generate several isoforms of N are also completely conserved (30,31). Whereas differences at amino acid positions 52 and 91 are located in the P-binding domain (23), they did not induce any deleterious effect on polymerase activity in the minireplicon assay (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…While BoDV-2 N contains 6 amino acid differences and an amino acid deletion not shared with BoDV-1 N (Fig. 2A), in addition to NLS and NES, which determine the intracellular localization of N (21,22), four amino acid residues thought to interact with viral RNA (29) are completely conserved in BoDV-2 N. Moreover, a downstream start codon and splicing donor and acceptor sites that generate several isoforms of N are also completely conserved (30,31). Whereas differences at amino acid positions 52 and 91 are located in the P-binding domain (23), they did not induce any deleterious effect on polymerase activity in the minireplicon assay (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of M and G is regulated by some transcriptional and post-transcriptional mechanisms in infected cells. First, the transcript encoding both the M and the G genes is transcribed as a polycistronic transcript that has the lowest expression level among the viral transcripts [18]. This polycistronic transcript then undergoes multiple alternative splicing events to mature into the separate mRNAs expressing M, G and L [19].…”
Section: Full-textmentioning
confidence: 99%
“…First, X/P transcripts may be rarely reverse-transcribed and/or integrated into the host genome. However, the amount of X/P transcript is comparable to that of the N transcript in cells infected with Borna disease virus 1 (BoDV-1), a modern orthobornavirus [8], suggesting that there is enough chance to be integrated into the host genome. Further, we experimentally demonstrated that X/P mRNA of BoDV-1 could be integrated into the host genomes [9].…”
Section: Introductionmentioning
confidence: 99%
“…First, X/P mRNA, which encodes the X and P proteins, may have a low propensity for reverse-transcription and/or integration into the host genome. However, previous studies of Borna disease virus 1 (BoDV-1; genus Orthobornavirus ) showed that X/P mRNA is the most abundant transcript among the viral mRNAs (11, 12), which should therefore provide enough chances for integration. Moreover, we have previously demonstrated that the X/P mRNA of BoDV-1 can be reverse-transcribed and integrated into the genome of host cells (3, 7).…”
Section: Introductionmentioning
confidence: 99%